Desarticulação interescapulotorácica em pacientes com tumores mamários. Revisão Sistemática da Literatura - Franca, Flávia Cardoso [UNESP] (Faculdade de Medicina de Botucatu, 2025)
INTRODUCTION: Forequarter amputation (FA) or Interscapulothoracic disarticulation is indicated in patients with invasive breast carcinoma (IBC) in selected cases: primary resection of a locally advanced or recurrent tumor, Stewart-Treves syndrome (STS), or sarcoma secondary to radiation due to breast cancer (radiation-induced sarcoma, RIS). However, no studies have robustly evaluated the indications, results, complications, recurrence and overall survival in the context of FA in patients with BC. MATERIAL AND METHODS: We performed a systematic review of 8 databases according to the PICOS and PRISMA methodology through December 31, 2022. The selection criteria were publications that included case series, reports or case series of patients with primary or recurrent IBC, STS or RIS, with indication for or undergoing FA. Patient data were collected on a standardized form, tabulated and analyzed in the IBM SPPS® for Mac® program. Descriptive statistics are presented, and Kaplan‒Meier survival curves were generated and compared with the log-rank method. RESULTS: We identified 54 articles and collected data from 100 patients. The intention of FA was curative for 48 patients (57.1%) and palliative in 32 (38.1%). The procedure was performed due to STS (35%), upper limb dysfunction (18%), lymphedema (10%), recurrent axillary tumors (10%) and RIS (9%). Complications were described in 10 cases, such as skin necrosis and pleural effusion; there were reports of pain relief after surgery, gratitude and physical/emotional well-being. The overall actuarial global survival rates at 12, 24, 36 and 60 months were 65.6%, 42.8%, 36.4% and 32.4%, respectively. The main factors associated with survival were tumor’s condition (p=0.05) and surgical intent (p<0.001; multivariate analysis). CONCLUSIONS: FA has few complications and attenuates symptoms in patients treated with both curative and palliative intent. Surgery is justified in select cases, such as locally advanced tumors, infiltration of axillary structures, upper limb lymphedema with loss of function, and STS and RIS, and often represents the best chance for local disease control.
Forequarter amputation for breast cancer. Systematic review and survival analysis
Keywords: Câncer de mama; Amputações; Desarticulação; Desarticulação interescapulotorácica; Amputação do quarto dianteiro; Síndrome de Stewart & Treves; Sarcoma radioinduzido